2019
DOI: 10.1002/mgg3.726
|View full text |Cite
|
Sign up to set email alerts
|

The human amniotic fluid mesenchymal stem cells therapy on, SKOV3, ovarian cancer cell line

Abstract: Purpose One of the most common malignancies peculiar to female health with few symptoms, low response to therapy, difficult diagnosis, frequent relapse, and high mortality, is ovarian cancer. Thus, our experiment, using Human amniotic fluid mesenchymal stem cells (hAFMSCs) as a therapeutic tool, aims to find an efficient treatment approach for patients suffering from SKOV3 ovarian cancer. Material & Methods In this study, we obtained 5 ml amniotic fluid from 16–20 week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 47 publications
(69 reference statements)
1
19
0
Order By: Relevance
“…MSCs are strong proliferation inhibitors of immune cells like the natural killer cells (NK cells). The same results have been reported on numerous cancer types such as breast cancer [ 45 ], hepatoma [ 46 ], ovarian cancer [ 23 ], and glioma [ 47 ]. It is reported that MSCs exert their growth inhibitory effect through MSC-secreted prostaglandin E2 (PGE2), IL-6, indoleamine2,3- dioxygenase (IDO), TGF-β1, and NO [ 48 , 49 ].…”
Section: Tumor-suppressing Effects Of Hamscs/hafmscssupporting
confidence: 80%
See 1 more Smart Citation
“…MSCs are strong proliferation inhibitors of immune cells like the natural killer cells (NK cells). The same results have been reported on numerous cancer types such as breast cancer [ 45 ], hepatoma [ 46 ], ovarian cancer [ 23 ], and glioma [ 47 ]. It is reported that MSCs exert their growth inhibitory effect through MSC-secreted prostaglandin E2 (PGE2), IL-6, indoleamine2,3- dioxygenase (IDO), TGF-β1, and NO [ 48 , 49 ].…”
Section: Tumor-suppressing Effects Of Hamscs/hafmscssupporting
confidence: 80%
“…Some studies have revealed that hAMSCs/hAFMSCs induced tumor growth and metastasis [ 22 ]. However, reports confirming the anti-cancer effects of these cells are also available in literature [ 23 , 24 ]. The controversial results and poor understanding of mechanisms behind the effect of hAMSCs/hAFMSCs on cancer cells hamper those researchers who are trying to use such cells in clinic [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endometrial MSC show anti-cancer effects on human epithelial ovarian cancer cells in vitro and in vivo through paracrine factors [ 92 ]. Human amniotic fluid MSC (hAFMSC), which can be obtained by amniocentesis in the second trimester or at the end of pregnancy [ 93 ], have natural tumor tropism towards ovarian cancer cells, and by releasing soluble factors have an efficient anticancer effect on them [ 94 ]. More recently, human uterine cervical stem cells (hUCESC) or their secretome have shown a potent antitumor effect on HeLa cells, highly proliferating breast cancer cells and cancer-associated fibroblasts [ 42 ].…”
Section: Heterogeneity Among Msc From Different Postnatal Nichesmentioning
confidence: 99%
“…Nanofibrous structured scaffolds has been shown to favorably support bone tissue (osteoblast, osteoclast, and fibroblast) proliferation and differentiation in 3D cell cultures for possible implantation . In a recent report on breast cancer, it was revealed that a 3D nanofiber scaffold exerted significant influence on CD44+/CD24− by limiting their migration and invasion tendencies thus further highlighting the importance of cell‐extracellular matrix interaction in stem cell proliferation, which could be exploited for designing therapeutic interventions with better efficacies …”
Section: D Nanoscaffold Developmentmentioning
confidence: 99%
“…52,53 In a recent report on breast cancer, it was revealed that a 3D nanofiber scaffold exerted significant influence on CD44+/CD24− by limiting their migration and invasion tendencies thus further highlighting the importance of cell-extracellular matrix interaction in stem cell proliferation, which could be exploited for designing therapeutic interventions with better efficacies. 54,55 7 | CLINICAL APPLICATIONS OF SOME NANOMATERIALS…”
Section: Developmentmentioning
confidence: 99%